Coccolithophore response to modern and past ocean acidification events - Berger, Christine (2013)
The absorption of the recent rising atmospheric CO2 alters the oceans carbonate system and affects the living conditions for marine calcifiers. Coccolithophores as major calcifying phytoplankton largely contribute to the modern carbonate production and play an important role in the global carbon cycle. Thus, changes in the calcite production of the coccolithophores have an impact on the carbon cycle. The effect of ocean acidification on coccolithophore calcification has been observed in several types of experimental, field, and sediment studies, even in combination with other environmental factors, but most studies base on short-term laboratory experiments with single species or strains. Despite various results with species and strain specific response, the most frequent finding in recently conducted experiments is a decrease in coccolithophore calcification under future CO2 levels. In contrast to monospecific laboratory experiments, natural coccolithophore assemblages consist of a heterogenous composition with diverse species and morphotypes, adapted to various environmental conditions. In a natural assemblage changing seawater conditions can lead to a dominance shift to better adapted species or morphotypes with different coccolith weight or size. To gain insights into the possible impact on the carbon cycle due to changing coccolithophore calcification, the response of the entire assemblage to changing environmental conditions in recent and past oceans should be taken into account. The main objective of this thesis was to investigate coccolithophore calcification of the dominant coccolithophore family Noelaerhabdaceae in different past atmospheric CO2 scenarios to obtain the influence of the changing seawater carbonate chemistry and to untangle the response from other environmental factors. Coccolith weight estimates are suggested as a possible indicator to reconstruct calcification rates and were obtained with the automatic recognition system SYRACO. To examine the variability of Noelaerhabdaceae mean ...